Pengaruh Manajemen Sarana dan Prasarana Perpustakaan terhadap Kepuasan Peserta Didik di SMP Swasta Katolik Stella Maris Loli - Putri Suria Fridolin Sakan; Marlen Angela Daik; Nimrot Doke Para (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study erxaminers ther influerncer of library facility and infrastructurer managermernt on studernt satisfaction at Sterlla Maris Loli Catholic Privater Junior High School. A quantitativer merthod with a correrlational approach was employed to identify the relationship between the two variables. The analysis results reveal that the management of library facilities and infrastructure falls into an unsatisfactory category, with an average student satisfaction score of 49.3%. The t-test indicates a significant positive effect (t count = 9.040) between management and satisfaction levels, where 42% of student satisfaction can be explained by library management. Additionally, factors such as procurement, storage, and maintenance exacerbate the situation. These findings emphasize the need for improvements in library management, including better planning and adequate budget allocation. By enhancing the management of facilities and infrastructure, student satisfaction is expected to increase, consequently encouraging students to be more actively engaged in visiting the library. As a rercommerndation, ther school should derverlop a stratergic managermernt plan for ther library focuserd on improving serrvicer quality and facilities.